Georgian Biomedical News 2023
DOI: 10.52340/gbmn.2023.01.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy for Secondary Prevention After Myocardial Infarction in Antiplatelet-Naive High Cardiovascular Risk Patients with Non-Obstructive Coronary Artery Disease

Abstract: BACKGROUND.The growing evidence indicates the importance of non-obstructive coronary artery disease (NOCAD), with a high-risk of MACEs. The relevance of antiplatelet therapy is high and depends on a type of MINOCA. However, the effectiveness of different antiplatelet treatment regimens and secondary prevention strategies for patients with non-obstructive coronary artery disease is still unclear. OBJECTIVES In our previous cohort study, we found that secondary prevention with dual antiplatelet therapy with aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…[15][16][17][18]27 Our prior research results support previously published data on the lack of a secondary preventative effect of DAPT on one-year MACE in MINOCA patients with different cardiovascular risks. 19,28 Pending trial evidence about the usefulness of DAPT in MINOCA patients from ongoing MINOCA-BAT trial, 29 we decided to compare the long-term preventive effect of dual antiplatelet therapy with a monotherapy regimen in high cardiovascular risk (10-year ASCVD ≥20%) MINOCA patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18]27 Our prior research results support previously published data on the lack of a secondary preventative effect of DAPT on one-year MACE in MINOCA patients with different cardiovascular risks. 19,28 Pending trial evidence about the usefulness of DAPT in MINOCA patients from ongoing MINOCA-BAT trial, 29 we decided to compare the long-term preventive effect of dual antiplatelet therapy with a monotherapy regimen in high cardiovascular risk (10-year ASCVD ≥20%) MINOCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that DAPT had no secondary preventive effect on one-year cumulative MACCEs in MINOCA patients with high cardiovascular risks. 19 The neutral effect of dual antiplatelet therapy was observed during the second follow-up year; however, from the third year until the end of the follow-up, the preventive effect of DAPT on cumulative MACCEs significantly exceeded the effect of antiplatelet monotherapy with aspirin.…”
Section: Follow-upmentioning
confidence: 95%
See 1 more Smart Citation
“…Several antiplatelet agents such as aspirin, clopidogrel and cilostazol, either alone or in combination, have been reported to produce beneficial effects in diverse cardiovascular dis-eases including pulmonary hypertension [157,158], coronary artery abnormalities [159][160][161][162][163] and ventricular arrhythmias and atrial fibrillation [155,156,164]. Furthermore, the 5-HT 2A receptor antagonist, ketanserin, has been shown to improve hemodynamic and neurohumoral alterations in patients with heart failure [165,166].…”
Section: Role Of Serotonin In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%